RELATIONSHIP BETWEEN FAMILY SANITATION ATTITUDES AND STATUS NUTRITIONAL HEALTH FOR TODDLERS IN CIBEUREUM VILLAGE, CIMAHI CITY - Yuliana; Rahma Nursiam; Rahmadina Nurhanijah; Silvi Nuryanti (Jurnal Kesehatan Budi Luhur : Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2025)
Malnutrition among toddlers remains a major public health issue in Indonesia, including in Cimahi City. Family sanitation is suspected to be one of the contributing factors, as poor environmental hygiene can increase the risk of infections that impair nutrient absorption in children. This study aimed to examine the relationship between family sanitation attitudes and the nutritional status of infants and toddlers in Cibeureum RW 08, Cimahi City. A quantitative research design with a descriptive correlational approach was used. Data were collected through questionnaires assessing family sanitation attitudes and anthropometric measurements to evaluate nutritional status based on weight-for-age (W/A), weight-for-height (W/H), and height-for-age (H/A) indices. A total of 109 respondents were selected using purposive sampling. Data were analyzed using the Chi-square test. Results showed that 64 families (58.7%) had good sanitation attitudes, while 45 families (41.3%) had poor sanitation attitudes. Most toddlers (70.64%) had normal nutritional status, while 20.18% were malnourished and 7.34% undernourished. Statistical analysis revealed no significant association between family sanitation attitudes and toddlers' nutritional status (p = 0.894). In conclusion, while good family sanitation practices are important for disease prevention, they were not significantly associated with toddlers’ nutritional status in this study. Other factors such as feeding practices, dietary intake, and socioeconomic conditions may play a more prominent role and warrant further investigation. Keywords : Nutritional status, Toddler, Family sanitation